Circulating MicroRNAs From Plasma Small Extracellular Vesicles as Potential Diagnostic Biomarkers in Pediatric Epilepsy and Drug-Resistant Epilepsy - Wang, Yilong; Wang, Yeping; Chen, Yi; Hua, Yi; Xu, Lu; Zhu, Mengying; Zhao, Congying; Zhang, Weiran; Sheng, Guoxia; Liu, Liu; Jiang, Peifang; Yuan, Zhefeng; et al. (Frontiers in Molecular Neuroscience, 2022)
Pediatric epilepsy is a neurological condition that causes repeated and unprovoked seizures and is more common in one-to five-year-old children. Drug resistance has been indicated as a key challenge in improving the clinical outcomes of patients with pediatric epilepsy. In the present study, we aimed to identify serum small extracellular vesicles (sEVs) derived microRNAs (miRNAs) from the serum samples of children for predicting the prognosis in patients with epilepsy and drug-resistant epilepsy. A total of 90 children clinically diagnosed with epilepsy (46 antiepileptic drug (AED)-responsive epilepsy and 44 drug-resistant epilepsy) and 37 healthy controls (HCs) were enrolled in this study. RNA sequencing was performed to identify serum sEVs derived miRNAs isolated from the children’s serum samples. Differentially expressed serum sEVs derived miRNAs were identified using bioinformatics tools and were further validated by reverse transcription-polymerase chain reaction and receiver operator characteristic curve analysis. Heat maps showed characteristics of differentially expressed serum sEVs derived miRNAs between HCs and drug-responsive or drug-resistant epileptic children. In the present study, 6 miRNAs (hsa-miR-125b-5p, hsa-miR-150-3p, hsa-miR-199a-3p, hsa-miR-584-5p hsa-miR-199a-5p, and hsa-miR-342-5p) were selected for further validation. hsa-miR-584-5p, hsa-miR-342-5p, and hsa-miR-150-5p with area under curve (AUC) values of 0.846, 0.835, and 0.826, respectively, were identified as promising biomarkers of epilepsy. A logistic model combining three miRNAs (hsa-miR-584-5p, hsa-miR-342-5p, and hsa-miR-199a-3p) could achieve an AUC of 0.883 with specificity 0.969 and sensitivity 0.556 and a six miRNAs model (hsa-miR-342-5p, hsa-miR-584-5p, hsa-miR-150-5p, hsa-miR-125b-5p, hsa-miR-199a-3p, and hsa-miR-199a-5p) could attain an AUC of 0.888. The predicted probability of multiple miRNA panels was evaluated for differentiating between drug-resistant children and drug-responsive children. The AUC of a six-miRNA panel (hsa-miR-342-5p, hsa-miR-584-5p, hsa-miR-150-5p, hsa-miR-125b-5p, hsa-miR-199a-3p, and hsa-miR-199a-5p) reached 0.823 with specificity 0.967 and sensitivity 0.543. We identified and confirmed serum sEVs derived miRNA biomarkers that could be considered as potential therapeutic targets for pediatric epilepsy and drug-resistant epilepsy. Keywords: epilepsy, microRNAs, small extracellular vesicle, anti-epileptic drug resistance, anti-epileptic drug response